Accumulation of Heavy Metals in Mangrove Sediments of Chumphon Province, Thailand - Nathsuda Pumijumnong; Bussarin Uppadit (Applied Environmental Research, 2013)
The objective of this study was two-fold: to examine the heavy metal (Cd, Cu, Cr, Ni, Mn, Pb and Zn) levels that have accumulated in mangrove forest sediments in Chumphon Province, Thailand, and to determine the relationship between heavy metals and the physiochemical properties of sediment. The sediment was digested with HNO3 and HCl using a milestone microwave digestion system (model MLS-1200 MEGA), followed by the addition of 50 ml distilled water. The concentrations of Cu, Cr, Ni, Mn, and Zn in the filtered and digested samples were determined by air-acetylene flame atomic absorption spectrophotometry (FAAS, model Varian SpectrAA 220FS). Cd and Pb were analyzed by a graphite furnace atomic absorption spectrophotometer (GASS, model Varian SpectrAA220). The accumulation of heavy metals originated largely upstream and decreased towards the canal mouths. The highest levels of heavy metals were found at E-let canal (Thung Kha Bay). The heavy metals present in our study area, listed from the most to least prevalent, were Mn, Cu, Zn, Cr, Ni, Pb, and Cd. A striking relationship was found between heavy metal type and sediment physiochemical properties (pH, OM, EC, and CEC).